Hepatoprotective effects of peach gum polysaccharides against alcoholic liver injury: moderation of oxidative stress and promotion of lipid metabolism - Zhou, Bingjie; Liu, Pinpin; Yao, Xiangao; Cao, Huijie; Zhu, Hang; Wang, Qiao; Liu, Yan; Fang, Min; Wu, Yongning; Gong, Zhiyong (Frontiers in Nutrition, 2024)
Natural polysaccharides extracted from plants have received increasing attention due to their rich bioactivity. In our study, peach gum polysaccharides (PGPs) were extracted by water extraction-alcohol precipitation method. PGPs are typical pyranose polysaccharides with a mean molecular weight of 3.68 × 106 g/mol. The antioxidant activity and hepatoprotective capacity of PGPs were studied. In vitro, assays showed that PGPs scavenged DPPH, OH, and O2– in a dose-dependent manner. PGPs exhibited antioxidative properties against alcohol-induced HL7702 cells, as evidenced by the normalization of MDA, SOD, ROS, and GSH levels. To further elucidate the hepatoprotective mechanism of PGPs, we carried out in vivo experiments in male mice. PGPs exerted hepatoprotective effects in alcohol liver disease (ALD) mice by exerting antioxidant effects, decreasing the inflammatory response and modulating lipid metabolism. In addition, metabolomic analysis indicated that PGPs mainly regulate D-glutamine and D-glutamate metabolism, alanine, aspartate and glutamate metabolism, and arginine biosynthesis to promote hepatic metabolism and maintain body functions. Overall, this study revealed that the hepatoprotective mechanism of PGPs against ALD might be associated with the regulation of oxidative stress and lipid metabolism.